Defining the first preventive conservation guidelines for hand-painted magic lantern glass slides - Santos, Ângela (2022)
The authors acknowledge the support of the Portuguese Foundation for Science and Technology (FCT-MCTES), through the doctoral program CORES-PD/00253/2012, for the PhD grant PD/BD/136694/2018 (Ângela Santos), and Research Unit VICARTE (UIDB/00729/2020). This research has benefited from the use of the infrastructure PRISC (Portuguese Research Infrastructure of Scientific Collections). The authors are also grateful to all the institutions and individuals that accepted to participate in the online survey, and to the Portuguese Cinematheque – Museum of Cinema, and National Museum of Natural History and Science of the University of Lisbon for the collaboration with the project "Lanterna Magica – Technology and Preservation of Painted Glass Slides for Projection with Magic Lanterns". The authors would also like to acknowledge for the relevant comments of the reviewers that significantly contributed to the improvement of the manuscript.